Investigation of structural, electronic, magnetic, elastic and thermodynamic properties of Mn3GaN antiperovskite by first principle and Monte Carlo simulations. Issue 13 (3rd July 2021) - Azouaoui, A.; Benzakour, N.; Hourmatallah, A.; Bouslykhane, K.
ABSTRACT: Structural, electronic, magnetic, elastic and thermodynamic properties of Mn 3 GaN anti-perovskite have been studied using the first-principles calculations based on density functional theory (DFT) and Monte Carlo simulations within the Ising model. The structural investigation exposes the antiferromagnetic configuration stability of the compound. Also, the density of states (DOS) and band structure calculations show a metallic behaviour of Mn 3 GaN . The computed elastic constants, phonon dispersion and density phonon states calculations demonstrate that the Mn 3 GaN compound is mechanically and dynamically stable. The calculated results of Poisson's ratio, Pugh's ratio and Cauchy pressure show that the Mn 3 GaN is ductile material with a metallic bond. The thermodynamic parameters like heat capacity, Debye and melting temperature have also been calculated. The exchange coupling of Mn 3 GaN has been calculated to obtain the critical temperature ( T N ) from Monte Carlo calculations. The obtained value of T N (288 K) is in good agreement with other experimental and theoretical works.